A comparison of bone mineral densities among female athletes in impact loading and active loading sports - Fehling, P. C.; Alkel, L.; Clasey, J.; Rector, A.; Stillman, R. J. (Bone, 1995)
Bone mineral densities in college female athletes in volleyball (N = 8), gymnastics (N = 13), and swimming (N = 7) were compared to a control group (N = 17). A regional analysis of total body scans indicated the following. Gymnasts had significantly greater bone mineral density than the other groups at the right and left arm sites. The impact loading groups (gymnastics and volleyball) had greater bone mineral density in the legs and pelvis than the swimming and control groups. Both groups had significantly greater torso bone mineral density than the control group. There were no differences at any site between the swimming and control groups. Implication. Bone mineral density in women is only affected by impactful highly-exertional activities. General rhythmic moderately loaded activities, such as swimming, do not influence bone mineral density. (Bone, 17, 205-210)